A Visionary Review of Viksit Bharat for Indian Sustainable Growth - Rashmi Kokatnur; Shweta Mathad; Vishwaja Kadadevar, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
A revolutionary road scheme for the development and development of India through the centenary of the country’s independence is a visionary review of India for the sustainable improvement of India. The goal of this ambitious vision is to build a country that is socially inclusive, economically stable and environmentally durable. The purpose is to address the challenging circumstances and opportunities of the Viksit India 2047, which is based on the principles of development and equity, by fusing social welfare, environmental protection and economic success. Promoting entrepreneurship, developing technological innovation, and a skill-reforming economy is an important foundation of this vision. The value of incorporating in the distorted India 2047 has been emphasized, with focusing on the empowerment of adolescents, uplifting weaker people and reducing inequalities in areas and places. The purpose of this vision is to establish India as a global leader in permanent and justified development through cooperative efforts between public and commercial areas as well as civil society. Not only Viksit India 2047 is a successful development route, but it also shows India’s commitment to create a rich, inclusive and flexible future for its entire people.
Keywords: Economic Expansion; Self -Sufficiency; Environmental Stability; Technological Innovation; Good Governance; Viksit Bharat